2021
DOI: 10.3390/en14165082
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Performance of a Submersible Pump: Prediction of Recirculation, Vortex Formation, and Swirl Resulting from Off-Design Operating Conditions

Abstract: Like any other turbomachinery, it is essential that the hydraulic behavior and performance of mixed-flow pumps are evaluated way in advance prior to manufacturing. Pump performance relies heavily on the proper design of the intake structure. Intake structures should be accurately designed in order to minimize and avoid unnecessary swirl and vortex formations. Ensuring the optimum performance condition as well as predicting how a particular intake structure affects the efficiency of the pump often requires eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The research methods mainly use CFD technology and model tests (Wang et al, 2019a;Munih et al, 2020;Yang et al, 2022a) to study the internal and external characteristics and pressure pulsation of the pump device. The three-dimensional steady numerical analysis and structural optimization of the flow field in each flow structure (Lu et al, 2018;Arocena et al, 2021;Sun et al, 2021) have achieved fruitful research results. Zhang et al (2014) investigated the three-dimensional turbulent flow and the pressure fluctuation in a submersible axial-flow pump by adopting the RNG k-ε turbulence model and the SIMPLEC algorithm, with which the pressure pulsation distribution of the impeller inlet and outlet was obtained (Ji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The research methods mainly use CFD technology and model tests (Wang et al, 2019a;Munih et al, 2020;Yang et al, 2022a) to study the internal and external characteristics and pressure pulsation of the pump device. The three-dimensional steady numerical analysis and structural optimization of the flow field in each flow structure (Lu et al, 2018;Arocena et al, 2021;Sun et al, 2021) have achieved fruitful research results. Zhang et al (2014) investigated the three-dimensional turbulent flow and the pressure fluctuation in a submersible axial-flow pump by adopting the RNG k-ε turbulence model and the SIMPLEC algorithm, with which the pressure pulsation distribution of the impeller inlet and outlet was obtained (Ji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They investigated these using a combination of CFD and experimental methods, and it was found that the impeller vane outlet placement angle had a significant effect on the pump performance. Arocena et al [13] conducted a numerical study of the performance of submersible pumps. The prediction of backflow, vortex formation and cyclonic flow caused by off-design conditions was investigated using CFD simulations to verify the pump head, efficiency, flow rate and other characteristics derived in different inlet structure designs.…”
Section: Introductionmentioning
confidence: 99%
“…The Taguchi method was a remarkable handy tool in optimizing the ESP. Arocena et al [29] designed and analyzed the intake structure of a submersible pump numerically. Wei et al [30] investigated the influence of impeller gap drainage width on the performance of a low-specific-speed centrifugal pump, and the results revealed that using a smaller gap width could significantly improve the performance.…”
Section: Introductionmentioning
confidence: 99%